Semitransparent perovskite solar cell based on low-indium transparent electrode and preparation method of semitransparent perovskite solar cell

By adopting low-indium transparent electrode structure and magnetron sputtering process in translucent perovskite solar cells, the high cost and poor stability caused by indium tin oxide transparent electrodes are solved, and high-efficiency and low-cost perovskites are achieved. Solar cells significantly improve humidity and heat stability and photoelectric conversion efficiency.

CN119300604APending Publication Date: 2025-01-10NINGBO INST OF TECH ZHEJIANG UNIV ZHEJIANG
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411386853.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing translucent perovskite solar cells are made of transparent indium tin oxide, which leads to high costs and poor stability under long-term humid and heat conditions, making it difficult to meet the needs of large-scale production and environmental applications.

Method used

Using a low-indium transparent electrode structure, including a tin oxide-based transparent conductive film, the design of single-layer, double-layer or triple-layer structures combined with suitable interface contact layer materials can achieve high conductivity and low In content, and optimize the characteristics of the SnOx film. , Magnetically controlled sputtering process is used to prepare transparent electrodes to improve humidity and heat stability.

Benefits of technology

The cost reduction and stability of translucent perovskite solar cells have been achieved, the photoelectric conversion efficiency has been improved, and the humidity and heat stability has been significantly enhanced, making it suitable for large-area industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300604A_ABST
    Figure CN119300604A_ABST
Patent Text Reader

Abstract

The invention discloses a low-indium-content transparent electrode-containing semitransparent perovskite solar cell and a preparation method thereof, the transparent electrode of the existing semitransparent perovskite cell is optimally designed, and the traditional indium tin oxide transparent conductive film is completely or partially replaced in the first transparent electrode and / or the second transparent electrode; the problems that indium resources are scarce and the price is high are solved. According to the invention, the design of the transparent electrode with a single-layer, double-layer or three-layer structure is adopted, and a proper interface contact layer material is combined, so that the transparent electrode has high conductivity, low In content and excellent interface characteristics, and high efficiency, low cost and high damp-heat stability of the semitransparent perovskite cell are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode and a preparation method thereof. Background Art

[0002] Semi-transparent perovskite solar cells have the characteristics of double-sided power generation and have potential application prospects in high-efficiency stacked cells, photovoltaic building integration and transportation facility integrated photovoltaics [Advanced Materials, 2019, 1806474].

[0003] At present, the top and bottom transparent electrodes of most semi-transparent perovskite cells use indium tin oxide (ITO) thin films. ITO has stable performance and is very suitable for application in perovskite cells. With the continuous expansion of the production capacity of perovskite cells, the demand for ITO transparent conductive materials is increasing. Since indium oxide (In2O3) accounts for more than 90% of ITO materials, the reserves of rare metal indium are limited and the price is relatively expensive, which will seriously restrict the sustainable development of perovskite cells. It is estimated that when the production capacity of perovskite cells reaches tens of GW, the supply of indium can no longer meet the needs of the industry. Therefore, it is very important to develop other transparent conductive materials to replace indium tin oxide materials. In addition, since the main component of ITO material is indium oxide, when the battery works under long-term hot and humid conditions, the indium oxide material will become low-priced indium oxide with poor conductivity, which will affect the performance of the battery.

[0004] Tin oxide (SnO x )-based transparent electrode, which is low in cost and abundant in reserves, is the preferred alternative material system for ITO transparent electrodes. In the industry, fluorine-doped tin oxide (FTO) film prepared by spray pyrolysis is used as the bottom electrode of perovskite cells. However, the preparation of FTO materials requires high temperatures above 500°C, while the upper temperature limit of perovskite cells is 150°C. Therefore, the top electrode of the semi-transparent cell cannot use FTO film, and indium oxide-based transparent electrodes are still used. Moreover, the thicker FTO electrode (>500nm) will affect the transmittance, and the rough surface of FTO will affect the quality of the nanoscale carrier transport layer thereon. Therefore, the use of FTO film for the bottom electrode will affect the performance of the perovskite cell.

[0005] In summary, existing semi-transparent perovskite solar cells have problems such as high cost and poor long-term stability. Summary of the invention

[0006] In view of the problems of high cost and poor environmental stability of semi-transparent perovskite solar cells in the prior art, the present invention provides a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode and a preparation method thereof. The semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode has the advantages of low cost and good stability.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A semi-transparent perovskite solar cell based on a low-indium transparent electrode, which comprises, from bottom to top: a glass substrate, a first transparent electrode on the glass substrate, a first carrier transport layer, a perovskite film, a second carrier transport layer, a buffer layer, and a second transparent electrode;

[0009] The first transparent electrode and / or the second transparent electrode at least comprises a layer of tin oxide (SnO x )-based transparent conductive film; the first transparent electrode and / or the second transparent electrode is a single-layer structure, a double-layer structure or a three-layer structure;

[0010] The low indium content means that the content of In2O3 in the first transparent electrode and the second transparent electrode is 0-50wt%;

[0011] The first carrier transport layer is a hole transport layer or an electron transport layer, and the second carrier transport layer is an electron transport layer or a hole transport layer;

[0012] The semi-transparent perovskite solar cell is a pin inverted structure or a nip positive structure perovskite solar cell;

[0013] The perovskite film structural formula is Cs x (FA y MA 1-y ) 1-x Pb(I z Br 1-z )3, 0≤x<1; 0≤y≤1; 0≤z≤1;

[0014] The semi-transparent perovskite solar cell based on the low-indium-containing transparent electrode has a photoelectric conversion efficiency of 19.5-23.2% and an average visible light transmittance of 18.1-20.0%;

[0015] Compared with the existing semi-transparent perovskite cells using ITO transparent electrodes, it has better moisture and heat stability; after being placed at 30% humidity for 600 hours, it can still maintain the initial 89.5-96.6%; after being placed at 85°C for 600 hours, it can still maintain the initial 90.4-94.6%.

[0016] Furthermore, the first transparent electrode and / or the second transparent electrode is tin oxide (SnO x ) a transparent conductive film single-layer structure, wherein SnO x The thickness of the transparent conductive film is 50-500nm.

[0017] Further, the first transparent electrode and / or the second transparent electrode is / are an ITO / SnO x double-layer structure. In the double-layer structure, the thickness of the ITO thin film is 20 - 200 nm, and the SnO x thin film has a thickness of 50 - 500 nm.

[0018] Further, the first transparent electrode and / or the second transparent electrode is / are an ITO / SnO x / ITO, SnO x / ITO / SnO x triple-layer structure. In the triple-layer structure, the thickness of the ITO thin film is 20 - 200 nm, and the SnO x thin film has a thickness of 50 - 500 nm.

[0019] Further, the In2O3 content in the ITO thin film is 90 - 99 wt%.

[0020] Further, the SnO x conductive thin film is a pure SnO x thin film or a Ta-doped SnO x thin film (abbreviated as TTO). The SnO x thin film is a thin film with a low oxygen content, where 1 < x ≤ 2 and the O / Sn ratio is 1 - 2;

[0021] Further, the total mass ratio of tantalum oxide in the transparent conductive thin film is 0.5 - 10 wt%.

[0022] Further, the ITO-based thin film and the SnO x -based thin film are prepared by a magnetron sputtering process.

[0023] Further, the sputtering power density of the SnO x thin film in the first transparent electrode is 2 - 10 W / cm 2 , the gas pressure is 0.2 - 1 Pa, the substrate temperature is room temperature to 300 °C, the O2 / Ar ratio is 0 - 6%, and the film thickness is 50 - 500 nm.

[0024] Further, the sputtering power density of the ITO thin film in the first transparent electrode is 2 - 10 W / cm 2 , the gas pressure is 0.2 - 1.0 Pa, the substrate temperature is room temperature to 300 °C, the O2 / Ar ratio is 0 - 6%, and the film thickness is 20 - 200 nm.

[0025] Further, the sputtering power density of the SnO x thin film in the second transparent electrode is 2 - 8 W / cm 2, gas pressure 0.2-1Pa, substrate temperature is room temperature ~ 150℃, O2 / Ar ratio is 0-6%, and film thickness is 50-500nm.

[0026] Furthermore, the sputtering power density of the ITO film in the second transparent electrode is 2 to 8 W / cm 2 , gas pressure 0.2-1Pa, substrate temperature is room temperature ~ 150℃, O2 / Ar ratio is 0-6%, and film thickness is 20-200nm.

[0027] Furthermore, the first carrier transport layer in the nip positive structure is an electron transport layer, which is TiO2, SnO x , CPTA films, the second carrier transport layer is a hole transport layer, which is a Spiro-OMeTAD film, and the above films are prepared by chemical coating method.

[0028] Furthermore, the first carrier transport layer in the pin inversion structure is a hole transport layer, which is NiO x The second carrier transport layer is an electron transport layer, which is a PCBM / C60 composite film. The above films can be prepared by chemical coating, magnetron sputtering, thermal evaporation and other processes.

[0029] Furthermore, the buffer layer is an atomic layer deposition (ALD) SnO2 film;

[0030] Furthermore, the SnO2 film prepared by ALD is a stoichiometric SnO2 film, and the thickness of the ALD SnO2 film is 5-40nm.

[0031] The present invention also relates to a method for preparing the above-mentioned semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode, comprising the following steps:

[0032] S1, preparing a first transparent electrode with a single-layer, double-layer or triple-layer structure on a pretreated glass substrate;

[0033] The first transparent electrode is a single-layer SnO x Based on transparent conductive film, or double-layer structure SnO x / ITO film, or three-layer structure ITO / SnO x / ITO thin film, the thin film is prepared by using ceramic target and magnetron sputtering;

[0034] S2, sequentially depositing a first carrier transport layer, a perovskite film, a second carrier transport layer, and a buffer layer on the first transparent electrode;

[0035] The deposition is the deposition of a pin structure or a nip perovskite cell;

[0036] S3. Preparation of single-layer SnO on the buffer layer x Thin film or double layer SnO x / ITO film, or three-layer SnO x / ITO / SnO x The second transparent electrode of the thin film is used to obtain a semi-transparent perovskite solar cell based on a low indium-containing transparent electrode.

[0037] Furthermore, the pretreatment of the glass substrate in step S1 is to wash it with deionized water, acetone and isopropanol in sequence for 10 to 30 minutes.

[0038] Furthermore, in the pin structure described in step S2, the first carrier transport layer in the pin inversion structure is NiO x , P3CT, P3HT, PACz films, the second carrier transport layer is a PCBM / C60 composite film, and the above films can be prepared by chemical coating, thermal evaporation, magnetron sputtering and other processes.

[0039] Furthermore, in the nip perovskite battery described in step S2, the first carrier transport layer in the nip positive structure is TiO2, SnO x , CPTA films, the second carrier transport layer is a Spiro-OMeTAD film, and the above films are prepared by chemical coating method.

[0040] Furthermore, the buffer layer in step S2 is an atomic layer deposited SnO2 film, and the thickness of the SnO2 film is 5-40nm.

[0041] Furthermore, the second transparent electrode in step S3 is a single-layer structure SnO x Based on transparent conductive film, or double-layer structure SnO x / ITO film, or three-layer SnO x / ITO / SnO x The film is prepared by magnetron sputtering at low temperature using ceramic targets.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] 1. The semi-transparent perovskite solar cell based on a low-indium transparent electrode described in the present invention optimizes the transparent electrode of the existing semi-transparent perovskite cell, and completely or partially replaces the traditional indium tin oxide transparent conductive film in the first transparent electrode and / or the second transparent electrode, thereby solving the problem of scarce indium resources and high prices. The present invention adopts a single-layer, double-layer, or three-layer structure transparent electrode design, and combines a suitable interface contact layer material to achieve a transparent electrode with high conductivity, low In content, and excellent interface characteristics, thereby achieving high efficiency and low cost of semi-transparent perovskite cells.

[0044] 2. The semi-transparent perovskite solar cell based on a low-indium transparent electrode described in the present invention adopts methods such as doping atom substitution and oxygen vacancy concentration control to achieve the SnOx film with high conductivity and high transmittance, solve the problem of high square resistance of tin oxide-based transparent conductive film, and improve the photoelectric conversion efficiency of semi-transparent cells. In the semi-transparent perovskite solar cell based on a low-indium transparent electrode described in the present invention, the SnOx film in the second transparent electrode is in contact with the buffer layer ALD SnO2 film, which can achieve more excellent contact characteristics, including lower contact resistance and more matched energy levels, thereby improving the photoelectric conversion efficiency of semi-transparent cells.

[0045] 3. The semi-transparent perovskite solar cell based on a low-indium transparent electrode described in the present invention has higher wet-heat stability than the ITO film because Sn-O is stronger than In-O, thereby improving the wet-heat stability of the semi-transparent perovskite cell.

[0046] 4. The present invention describes a method for preparing a semi-transparent perovskite solar cell based on a low-indium transparent electrode, wherein the transparent electrode material is prepared by a magnetron sputtering process, which is the same as the existing process and does not introduce additional steps. The process is simple, the effect is obvious, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram of the structure of a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode with a single-layer structure of the first / second transparent electrode in Experimental Example 1 of the present invention;

[0048] Figure 2 It is a schematic diagram of the structure of a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode with a double-layer structure of the first / second transparent electrode in Experimental Example 8 of the present invention;

[0049] Figure 3 It is a schematic diagram of the structure of a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode with a three-layer structure of the first / second transparent electrode in Experimental Example 11 of the present invention;

[0050] Figure 4It is an initial efficiency diagram and transmittance curve diagram of a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode obtained in Experimental Example 1 of the present invention;

[0051] Figure 5 A graph showing the wet-heat stability of a semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode obtained in Experimental Example 1 of the present invention.

[0052] Description of the numbers in the figure:

[0053] 1. Glass substrate; 2. First transparent electrode single-layer SnO2 film; 3. First carrier transport layer; 4. Perovskite film; 5. Second carrier transport layer; 6. Buffer layer; 7. Second transparent electrode single-layer SnO x Thin film; 8. First transparent electrode double layer SnO x / ITO film; 9. The second transparent electrode double layer SnO x / ITO film; 10. The first transparent electrode has three layers of ITO / SnO x / ITO film; 11. The second transparent electrode has three layers of SnO x / ITO / SnO x film. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.

[0055] Embodiment 1:

[0056] The structural schematic diagram of a semi-transparent perovskite solar cell based on a low-indium transparent electrode of this embodiment is shown in FIG. Figure 1 As shown, from bottom to top, it includes: a glass substrate 1, a first transparent electrode layer 2 is a single layer of SnO x The first carrier transport layer 3 is PACz, the perovskite film layer 4 is PVK, the second carrier transport layer 5 is C60, the buffer layer 6 is ALD SnO2, and the second transparent electrode 7 is a single layer SnO x film;

[0057] The thickness of the glass substrate 1 is 1.1 mm; the first transparent electrode 2 is a single layer of SnO x The thickness of the film is 100nm; the thickness of each layer in PACz / PVK / C60 is 10nm, 350nm, and 30nm respectively; the thickness of the buffer layer ALD SnO2 film is 20nm; the second transparent electrode 7 is a single layer SnO x The film thickness is 200 nm.

[0058] A method for preparing a semi-transparent perovskite solar cell based on a low-indium transparent electrode of this embodiment comprises the following steps:

[0059] S1. The glass substrate was first cleaned with deionized water, acetone and isopropanol for 20 min respectively; a single-layer SnO2 transparent electrode layer 2 was prepared on the glass substrate by magnetron sputtering. The vacuum degree of the cavity during sputtering was 8×10 -4 Pa, using pure SnO x The target material was sputtered with a radio frequency sputtering power of 60 W, a substrate temperature of 150° C., a mixed atmosphere of 1% oxygen / argon, and a pressure of 0.3 Pa to obtain a 100 nm first transparent electrode layer 2; the sample was then transferred to a nitrogen glove box;

[0060] S2. Spin coating the first transparent electrode layer 2 at a speed of 3000 rpm for 30 seconds, spin coating PACz to prepare the first carrier transport layer 3, the PACz hole transport layer thickness is 10 nm, and annealing at 100 ° C for 10 minutes after spin coating;

[0061] The perovskite film layer 4 is prepared by spin coating a (FA0.97MA0.03)0.94Cs0.06Pb(I0.98Br0.02)3 film on PACz. The process of preparing the perovskite film layer 4 can be as follows:

[0062] 22.5mg CsI, 227mg FAI, 3.8mg MABr, 10mg MACl, 12.9mg PbBr2 and 781.4mg PbI2 were dissolved in 1.4ml DMF and DMSO mixed solvent with a volume ratio of 6:1 to form a 1.0M (FA0.97MA0.03)0.94Cs0.06Pb(I0.98Br0.02)3 perovskite precursor solution; the precursor solution was spin-coated at 5000rpm for 30s, and the film was treated with 150mL CB 20s before the end, and then the film was annealed at 120°C for 20min; the thickness of the final perovskite film was 350nm;

[0063] The sample is transferred to the thermal evaporation chamber, 30 nm C60 is evaporated on the perovskite film layer 4, and the second carrier transport layer 5 is prepared;

[0064] In an atomic layer deposition chamber, a SnO2 film is prepared on the second carrier transport layer 5 as a buffer layer 6. Tetrakis(dimethylamino)tin (TDMAS) and water are used as gas sources during deposition. The substrate temperature is 100°C. The deposition is repeated for 1500 cycles to obtain an ALDSnO2 film with a thickness of 20 nm.

[0065] S3. Sputtering a single layer of SnO on the buffer layer 6 x As the second transparent electrode layer 7, the vacuum degree of the cavity body during sputtering is 8×10 -4Pa, 20W low power sputtering is first used during RF sputtering, and then 60W high power sputtering is used, the substrate temperature is room temperature, the mixed atmosphere of 1% oxygen / argon, the pressure is 0.3Pa, and a 200nm second transparent electrode layer 7 is obtained;

[0066] Finally, the first and second transparent electrodes are made into single-layer SnO x Thin-film semi-transparent perovskite solar cells based on low-indium-containing transparent electrodes.

[0067] Figure 4 The graphs are photoelectric conversion efficiency and transmittance curves. The photoelectric conversion efficiency of the semi-transparent perovskite solar cell based on the low-indium-containing transparent electrode is 20.0%, and the average visible light transmittance is 19.3%.

[0068] Figure 5 This is an environmental stability diagram at 85°C and 30% humidity. A semi-transparent perovskite solar cell based on a low-indium-containing transparent electrode prepared in this embodiment uses a single-layer SnO2 transparent electrode, which has better wet-heat stability than the existing semi-transparent perovskite cell using an ITO transparent electrode; it can still maintain 96.6% of the initial value after being placed at 30% humidity for 600 hours; it can still maintain 94.6% of the initial value after being placed at 85°C for 600 hours.

[0069] Embodiment 2:

[0070] The difference from Example 1 is that Ta-doped SnO x Ta-doped SnO obtained by target sputtering x The other steps are the same as those in Example 1.

[0071] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 21.1% and an average visible light transmittance of 18.3%.

[0072] After being placed at 30% humidity for 600 hours, it can still maintain 95.2% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 93.5% of the initial value.

[0073] Embodiment 3:

[0074] The difference from Example 1 is that the first transparent electrode layer 2 is ITO, and the second transparent electrode layer 7 is a single layer of SnO x The other steps are the same as those in Example 1.

[0075] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 21.3% and an average visible light transmittance of 20.0%.

[0076] After being placed at 30% humidity for 600 hours, it can still maintain 91.5% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 92.2% of the initial value.

[0077] Embodiment 4:

[0078] The difference from Example 1 is that the single layer SnO x The thickness of the film is 200 nm, and the other steps are the same as in Example 1.

[0079] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 20.8% and an average visible light transmittance of 18.1%.

[0080] After being placed at 30% humidity for 600 hours, it can still maintain 96.0% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 94.5% of the initial value.

[0081] Embodiment 5:

[0082] The difference from Example 1 is that the second transparent electrode layer 7 has a single layer of SnO x The thickness of the film is 100 nm, and the other steps are the same as in Example 1.

[0083] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 19.5% and an average visible light transmittance of 20.0%.

[0084] After being placed at 30% humidity for 600 hours, it can still maintain 95.7% of the initial value; after being placed at 85℃ for 600 hours, it can still maintain 93.6% of the initial value.

[0085] Embodiment 6:

[0086] The difference from Example 1 is that the thickness of the buffer layer ALD SnO2 film is changed to 10 nm, and the other steps are the same as Example 1.

[0087] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 19.7% and an average visible light transmittance of 19.6%.

[0088] After being placed at 30% humidity for 600 hours, it can still maintain 92.2% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 93.4% of the initial value.

[0089] Embodiment 7:

[0090] The difference from Example 1 is that a perovskite cell with a nip structure is used, and the other steps are the same as Example 1.

[0091] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 22.8% and an average visible light transmittance of 18.2%.

[0092] After being placed at 30% humidity for 600 hours, it can still maintain 89.5% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 90.4% of the initial value.

[0093] Embodiment 8:

[0094] The structural schematic diagram of a semi-transparent perovskite solar cell based on a low-indium transparent electrode of this embodiment is shown in FIG. Figure 2 shown.

[0095] The difference from Example 1 is that the first transparent electrode layer 2 is SnO x / ITO double-layer film, thickness is 80 / 20nm; the second transparent electrode layer 7 is SnO x / ITO film with a thickness of 80 / 120 nm, and other steps are the same as in Example 1.

[0096] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 21.8% and an average visible light transmittance of 20.0%.

[0097] After being placed at 30% humidity for 600 hours, it can still maintain 94.6% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 93.9% of the initial value.

[0098] Embodiment 9:

[0099] The difference from Example 1 is that the first transparent electrode layer 2 is SnO x / ITO double-layer film, thickness is 80 / 20nm; the second transparent electrode layer 7 is still a single layer of SnO x The film has a thickness of 200 nm and the other steps are the same as those in Example 1.

[0100] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 21.4% and an average visible light transmittance of 19.6%.

[0101] After being placed at 30% humidity for 600 hours, it can still maintain 95.1% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 94.2% of the initial value.

[0102] Embodiment 10:

[0103] The difference from Example 1 is that the second transparent electrode layer 7 is SnO x / ITO film, thickness is 80 / 120nm; the first transparent electrode layer 2 is still SnO xThe film has a thickness of 100 nm and the other steps are the same as those in Example 1.

[0104] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 21.4% and an average visible light transmittance of 19.7%.

[0105] After being placed at 30% humidity for 600 hours, it can still maintain 94.6% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 94.2% of the initial value.

[0106] Embodiment 11:

[0107] The structural schematic diagram of a semi-transparent perovskite solar cell based on a low-indium transparent electrode of this embodiment is shown in FIG. Figure 3 shown.

[0108] The difference from Example 1 is that the first transparent electrode layer 2 is ITO / SnO x / ITO three-layer film, thickness is 20 / 60 / 20nm; the second transparent electrode layer 7 is SnO x / ITO / SnO x Three-layer film with thickness of 50 / 100 / 50 nm, other steps are the same as Example 1.

[0109] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 23.2% and an average visible light transmittance of 19.9%.

[0110] After being placed at 30% humidity for 600 hours, it can still maintain 94.8% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 93.7% of the initial value.

[0111] Embodiment 12:

[0112] The difference from Example 1 is that the first transparent electrode layer 2 is ITO / SnO x / ITO three-layer film, thickness is 20 / 60 / 20nm; the second transparent electrode layer 7 is still a single layer of SnO x The film has a thickness of 200 nm and the other steps are the same as those in Example 1.

[0113] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 22.8% and an average visible light transmittance of 19.5%.

[0114] After being placed at 30% humidity for 600 hours, it can still maintain 95.6% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 94.2% of the initial value.

[0115] Embodiment 13:

[0116] The difference from Example 1 is that the second transparent electrode layer 7 is SnO x / ITO / SnO x Three-layer film with thickness of 50 / 100 / 50nm; the first transparent electrode layer 2 is still a single layer of SnO x The film has a thickness of 100 nm and the other steps are the same as those in Example 1.

[0117] The semi-transparent perovskite solar cell based on low-indium transparent electrode has a photoelectric conversion efficiency of 22.7% and an average visible light transmittance of 19.4%.

[0118] After being placed at 30% humidity for 600 hours, it can still maintain 94.9% of the initial value; after being placed at 85°C for 600 hours, it can still maintain 94.1% of the initial value.

[0119] Comparative Example:

[0120] The difference from Example 1 is that a single layer of ITO film is used as the first / second transparent electrode.

[0121] The photoelectric conversion efficiency of the prepared semi-transparent perovskite solar cell is 21.1%, and the average visible light transmittance is 21.5%; after being placed at 30% humidity for 600 hours, it can still maintain the initial 90.1%; after being placed at 85°C for 600 hours, it can still maintain the initial 91.1%.

[0122] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode, characterized in that: From bottom to top: glass substrate, first transparent electrode on the glass substrate, first carrier transport layer, perovskite film, second carrier transport layer, buffer layer, second transparent electrode; The first transparent electrode and / or the second transparent electrode at least comprises a layer of tin oxide-based transparent conductive film; the first transparent electrode and / or the second transparent electrode is a single-layer structure, a double-layer structure or a triple-layer structure; The low indium content means that the content of In2O3 in the first transparent electrode and the second transparent electrode is 0-50wt%; The first carrier transport layer is a hole transport layer or an electron transport layer, and the second carrier transport layer is an electron transport layer or a hole transport layer; The semi-transparent perovskite solar cell is a pin inverted structure or a nip positive structure perovskite solar cell; The perovskite film structural formula is Cs x (FA y MA 1-y ) 1-x Pb(I z Br 1-z )3, 0≤x<1; 0≤y≤1; 0≤z≤1; The semi-transparent perovskite solar cell based on the low-indium-containing transparent electrode has a photoelectric conversion efficiency of 19.5-23.2% and an average visible light transmittance of 18.1-20.0%; Compared with the existing semi-transparent perovskite cells using ITO transparent electrodes, it has better moisture and heat stability; after being placed at 30% humidity for 600 hours, it can still maintain the initial 89.5-96.6%; after being placed at 85°C for 600 hours, it can still maintain the initial 90.4-94.6%.

2. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode according to claim 1, characterized in that: The first transparent electrode and / or the second transparent electrode is SnO x Single-layer structure; in the single-layer structure, SnO x The thickness of the transparent conductive film is 50-500nm.

3. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode according to claim 1, characterized in that: The first transparent electrode and / or the second transparent electrode are ITO / SnO x Double-layer structure, in which the ITO film thickness is 20-200nm, SnO x The film thickness is 50-500nm.

4. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode according to claim 1, characterized in that: The first transparent electrode and / or the second transparent electrode are ITO / SnO x / ITO、SnO x / ITO / SnO x Three-layer structure; in the three-layer structure, the thickness of the ITO film is 20-200nm, the SnO x The film thickness is 50-500nm; the In2O3 content in the ITO film is 90-99wt%.

5. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode according to claim 1, characterized in that: The described SnO x conductive film is a pure SnO x film or a Ta-doped SnO x film. The SnO x film is a film with a low oxygen content, 1 < x ≤ 2, and the O / Sn ratio is 1 to 2; The total mass of the tantalum oxide accounts for 0.5-10wt% of the transparent conductive film.

6. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode according to claim 1, characterized in that: The ITO-based film, SnO x The base film is prepared by magnetron sputtering process: The first transparent electrode contains SnO x Sputtering power density of thin film: 2~10W / cm 2 , gas pressure 0.2-1Pa, substrate temperature room temperature ~ 300℃, O2 / Ar ratio 0-6%, film thickness 50-500nm; The sputtering power density of the ITO film in the first transparent electrode is 2-10 W / cm 2 , gas pressure 0.2-1.0Pa, substrate temperature room temperature ~ 300℃, O2 / Ar ratio 0-6%, film thickness 20-200nm; The second transparent electrode SnO x Sputtering power density of thin film is 2~8W / cm 2 , gas pressure 0.2-1Pa, substrate temperature room temperature ~ 150℃, O2 / Ar ratio 0-6%, film thickness 50-500nm; The sputtering power density of the ITO film in the second transparent electrode is 2-8 W / cm 2 , gas pressure 0.2-1Pa, substrate temperature is room temperature ~ 150℃, O2 / Ar ratio is 0-6%, and film thickness is 20-200nm.

7. A semi-transparent perovskite solar cell based on a low indium-containing transparent electrode according to claim 1, characterized in that: The first carrier transport layer in the nip positive structure is an electron transport layer, which is TiO2, SnO x , one or more of CPTA films, the second carrier transport layer is a hole transport layer, which is a Spiro-OMeTAD film, and the above film is prepared by chemical coating method; The first carrier transport layer in the pin inversion structure is a hole transport layer, which is NiO x , P3CT, P3HT, PACz thin films or more, the second carrier transport layer is an electron transport layer, which is a PCBM / C60 composite thin film; the above thin films can be prepared by chemical coating, magnetron sputtering, thermal evaporation and other processes; The buffer layer is an atomic layer deposited SnO2 film; the SnO2 film prepared by atomic layer deposition is a stoichiometric ratio SnO2 film, and the thickness of the ALD SnO2 film is 5-40nm.

8. A method for preparing a semi-transparent perovskite solar cell based on a low-indium transparent electrode according to any one of claims 1 to 7, comprising the following steps: S1, preparing a first transparent electrode with a single-layer, double-layer or triple-layer structure on a pretreated glass substrate; The first transparent electrode is a single-layer SnO x Based on transparent conductive film, or double-layer structure SnO x / ITO film, or three-layer structure ITO / SnO x / ITO thin film, the thin film is prepared by using ceramic target and magnetron sputtering; S2, sequentially depositing a first carrier transport layer, a perovskite film, a second carrier transport layer, and a buffer layer on the first transparent electrode; The deposition is the deposition of a pin structure or a nip perovskite cell; S3. Preparation of single-layer SnO on the buffer layer x Thin film or double layer SnO x / ITO film, or three-layer SnO x / ITO / SnO x The second transparent electrode of the thin film is used to obtain a semi-transparent perovskite solar cell based on a low indium-containing transparent electrode.

9. The method for preparing a semi-transparent perovskite solar cell based on a low-indium transparent electrode according to claim 8, characterized in that: The pretreatment of the glass substrate in step S1 is to wash it with deionized water, acetone and isopropanol in sequence for 10 to 30 minutes.

10. The method for preparing a semi-transparent perovskite solar cell based on a low-indium transparent electrode according to claim 8, characterized in that: The pin structure described in step S2, wherein the first carrier transport layer in the pin inversion structure is NiO x , P3CT, P3HT, PACz thin films or more, the second carrier transport layer is a PCBM / C60 composite thin film, the above thin films can be prepared by chemical coating, thermal evaporation, magnetron sputtering and other processes; The nip perovskite battery described in step S2, wherein the first carrier transport layer in the nip positive structure is TiO2, SnO x , CPTA film, the second carrier transport layer is a Spiro-OMeTAD film, and the above film is prepared by chemical coating method; The buffer layer in step S2 is an atomic layer deposited SnO2 film, and the thickness of the SnO2 film is 5-40nm; The second transparent electrode in step S3 is a single-layer structure SnO x Based on transparent conductive film, or double-layer structure SnO x / ITO film, or three-layer SnO x / ITO / SnO x The film is prepared by magnetron sputtering at low temperature using ceramic targets.

Citation Information

Cited By

  • Transparent electrode of silicon heterojunction solar cell and preparation method thereof

    CN121531819A